2010
DOI: 10.1038/ja.2010.115
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of vacuole disruption and independence of potassium ion efflux in fungicidal activity induced by combination of amphotericin B and allicin against Saccharomyces cerevisiae

Abstract: Allicin selectively enhances the fungicidal activity of amphotericin B (AmB). It also accelerates AmB-induced vacuole disruption but does not affect AmB-induced potassium ion efflux in Saccharomyces cerevisiae and Candida albicans. The fungicidal activity of AmB alone or combined with allicin was further evaluated based on the relationship among cell viability, vacuole disruption and potassium ion efflux in S. cerevisiae. Lethality and vacuole disruption caused by AmB alone were completely restricted when K + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…AmB-induced vacuole disruption is substantially enhanced by allicin, an allyl-sulfur compound isolated from garlic (Allium sativum L.) (Borjihan et al, 2009;Ogita et al, 2006Ogita et al, , 2009Ogita et al, , 2010aOgita et al, , 2010bOgita et al, , 2012. A similar pattern of vacuole disruption is more markedly observed with the polyol macrolide antibiotic niphimycin (NM; Fig.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…AmB-induced vacuole disruption is substantially enhanced by allicin, an allyl-sulfur compound isolated from garlic (Allium sativum L.) (Borjihan et al, 2009;Ogita et al, 2006Ogita et al, , 2009Ogita et al, , 2010aOgita et al, , 2010bOgita et al, , 2012. A similar pattern of vacuole disruption is more markedly observed with the polyol macrolide antibiotic niphimycin (NM; Fig.…”
Section: Introductionmentioning
confidence: 54%
“…Allicindependent enhancement of the vacuole-disruption activity of AmB depends on the presence of ergosterol in the fungal plasma membrane, as demonstrated by the resistance of an ergosterol-less S. cerevisiae mutant to the combined lethal effects of AmB and allicin (Ogita et al, 2010b). Additionally, S. cerevisiae and C. albicans cells were similarly protected against AmB-mediated lethality when the cells had been pretreated with exogenous ergosterol (Borjihan et al, 2009;Ogita et al, 2009).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…1,5,6 We observed vacuole membrane fragmentation as another AmB-induced lethal event in cells of Saccharomyces cerevisiae and C. albicans that was markedly enhanced in the presence of allicin, an allyl-sulfur compound from garlic ( Figure 1). [7][8][9][10][11] A similar vacuoletargeting fungicidal activity was also detected with polymyxin B, a bactericidal antibiotic, which was also amplified by allicin or by various ionophores, such as salinomycin and monensin. 12,13 Our screening experiment additionally showed that zwiebelane A, an organosulfur compound from onion bulbs, enhances the vacuoletargeting fungicidal activity of polymyxin B.…”
Section: Introductionmentioning
confidence: 72%
“…1-4 The leakage of K + seems essential for AmB lethality even if AmB-induced cell death inevitably depends on vacuole disruption, as the hypertonic condition achieved by the addition of K + and Mg 2+ into medium resulted in simultaneous protection from vacuole disruption and cell death. 11 AmB is less active on ergosterol-less mutants (erg6D) of C. albicans and Candida lusitaniae than wildtype strains. 24 This lower activity is thus explained by the loss of ergosterol, which is essential for the ion channel formation with AmB in the fungal plasma membrane, but may be also explained by the failure of AmB to penetrate through the plasma membrane to exert its direct disruptive action on vacuoles.…”
Section: Discussionmentioning
confidence: 98%